PANDANGAN KRIMINOLOGI TERHADAP RADIKALISME AGAMA - Ismail Rumadan (IAIN Ambon, 2018)
Violence in recent years is quite apprehensive, whether done by individuals, communities and college students. So also religious radicalism emerged from small groups to large groups. These groups have one view, that the present government is a corrupt, dishonest, and fearful government against the West. So there needs to be a justification group that fights a fair, clean and capable country against the west. The institution that was fought was named Darul Islam. According to them Darul Islam has been able to form a clean and fair government. The groups in their movement are in the name of Islam for the support of the Islamic world. In developing their mission, they set up schools and mosques. As well as his regular activities of preaching from the mosque to the mosque. From the view of criminology, the movements are soft and hard. However non-physical. Thus from the view of criminology, they continue to commit violence. Keywords: criminology, violence, religious radicalism